Penerapan Sanksi Pidana Terhadap Pengguna Jalan Raya Yang Menghalangi Kendaraan Prioritas Ditinjau Dari Perspektif Hukum Pidana: The Imposition of Criminal Sanctions Against Road Users Who Obstruct Priority Vehicles From a Criminal Law Perspective - Mohammad Izza Fathony; Yudha Bagus Tunggala Putra Tunggala Putra (CLEAR: Criminal Law Review, 2024)
The increasing number of road users and the rise in private vehicle ownership have led to traffic congestion, which in turn obstructs the movement of priority vehicles performing their essential duties and functions. Moreover, there are individuals who intentionally impede the passage of these priority vehicles. Although such incidents have been followed up by the authorities, cases of obstructing priority vehicles continue to occur. Many instances of obstructing priority vehicles have been addressed by the police, yet these processes often end in peaceful settlements, despite the fact that such actions can lead to significant consequences. In principle, the obligation to grant priority to certain vehicles is stipulated in Article 134 of the Road Traffic and Transportation Law (UU LLAJ). However, there is no regulation imposing sanctions on individuals who obstruct priority vehicles while they are carrying out their duties. Padatnya pengguna jalan yang menggunakan fasilitas jalan serta bertambahnya pengguna kendaraan pribadi mengakibatkan kepadatan lalu lintas laju yang mengakibatkan laju kendaraan prioritas yang sedang melakukan tugas pokok dan fungsinya menjadi terhambat. Bahkan terdapat oknum – oknum yang dengan sengaja menghalangi laju kendaraan prioritas tersebut. Meski telah ditindak lanjuti peristiwa menghalangi kendaraan prioritas masih terjadi. Banyak kasus tentang menghalangi kendaraan prioritas yang telah ditindak lanjuti oleh pihak kepolisian namun, proses tersebut hanya berakhir dengan kata damai, padahal perbuatan menghalangi kendaraan tersebut dapat mengakibatkan dampak yang besar. Sejatinya, ketentuan untuk memberikan hak utama kendaraan tertentu telah diatur dalam Pasal 134 UU LLAJ, namun tidak ada peraturan yang memberikan sanksi kepada orang yang menghalangi kendaraan prioritas yang sedang melakukan tugas pokok dan fungsinya